Spatio-Temporal Distribution of Supra-Glacial Ponds and Ice Cliffs on Verde Glacier, Chile - Loriaux, Thomas; Ruiz, Lucas (Frontiers in Earth Science, 2021)
Known for their important role in locally enhancing surface melt, supraglacial ponds and ice cliffs are common features on debris-covered glaciers. We use high resolution satellite imagery to describe pond-cliff systems and surface velocity on Verde debris-covered glacier, Monte Tronador, and Southern Chile. Ponds and ice cliffs represent up to 0.4 and 2.7% of the glacier debris-covered area, respectively. Through the analyzed period and the available data, we found a seasonality in the number of detected ponds, with larger number of ponds at the beginning of the ablation season and less at the end of it. Using feature tracking, we determined glacier surface velocity, finding values up to 55 m/yr on the upper part of the debris-covered area, and decreasing almost to stagnation in the terminus. We found that larger ponds develop in glacier zones of low velocity, while zones of high velocity only contain smaller features. Meanwhile, ice cliffs appeared to be less controlled by surface velocity and gradient. Persistent ice cliffs were detected between 2009 and 2019 and backwasting up to 24 m/yr was measured, highlighting significant local glacier wastage.